ANTI-CORRUPTION EDUCATION FOR STUDENTS AT THE ORPHANAGE, DAU DISTRICT, MALANG REGENCY - Setiawan, Andi; Bachtiar, Rizqi (Wisesa: Jurnal Pengabdian Masyarakat, 2022)
Corruption is a form of extraordinary crime that has a very massive impact. Not only destroying economic stability and harming the people, corruption can also undermine all parts of the country. Therefore, eradicating corruption should be an important agenda in this country. The responsibility for eradicating corruption should also be carried out by all parties, not only by the KPK as a state institution that focuses on eradicating corruption. Various parties, ranging from the government, the private sector, organizations, to the entire community must also participate in eradicating and preventing corruption. So far, there are several approaches in the anti-corruption movement, one of which is through anti-corruption education. Anti-corruption education aims to prevent corruption by fostering and strengthening anti-corruption attitudes in society. One of the targets of anti-corruption education is students from elementary to high school levels. In this community service activity, the service team selected orphanage students in Dau District, Malang Regency, as targets for anti-corruption education. Anti-corruption education will be carried out through socialization with film screenings and inviting students to play three types of games, namely the “semai game”, “majo game”, and “puput LK game”. The results show that through the game, students more easily understand what actions are included in corruption and how to start practicing anti-corruption attitudes and values.